Banal Utopia: urban gardening as a practice for materialising utopic city spaces - Niala, JC (2022)
This thesis explores urban gardening as a banal practice that underpins the manifestation of utopian spaces within cities. Growing in Oxford on allotments and guerrilla gardening sites has increased both in practice and significance. This is due to the convergence of food provenance issues, environmental concerns, and the advent of the COVID-19 pandemic. This thesis combines the concepts of banal nationalism (a term proposed by Michael Billig (1995) which speaks to everyday practices through which humans build a shared sense of national identity) and utopia to propose the idea ‘banal utopia’ revealing the manner in which materialising a utopia is both quotidian and continual. Utopia is not a destination at which to arrive but is in a constant state of production and renewal that carries echoes of the gardening calendar.